2021
DOI: 10.31539/joting.v3i1.2074
|View full text |Cite
|
Sign up to set email alerts
|

Stimulus Taktil Kinestetik terhadap Perubahan Fisiologis Bayi Prematur dengan Perawatan Metode Kanguru

Abstract: Penelitian ini bertujuan untuk mengetahui pengaruh Stimulus Taktil Kinestetik (STK) terhadap perubahan fisiologis bayi prematur yang memperoleh Perawatan Metode Kanguru (PMK). Desain penelitian yang digunakan adalah Quasi Experiment dengan pretest-posttest two-group design. Sampel yang digunakan adalah sebanyak 39 bayi prematur yang dipilih dengan simple random sampling. Kelompok intervensi 20 bayi prematur dilakukan STK dengan durasi 15 menit dan kelompok kontrol 19 bayi prematur tanpa perlakuan. Pengukuran f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The results of the study of Hastuti and Marnita, et al showed that the physiological development of infant breathing after treatment (post) in the intervention and control groups showed that there were significant differences in BBLR Infant Breathing after treatment (post) both in the intervention group and the control group. The results of this study showed that tactile-kinesthetic stimulation interventions affected infant breathing where the breathing of infants who were given tactile-kinesthetic stimulation was more stable than infants who were not stimulated, which was seen in the intervention group of average respiration before the intervention 11 .…”
Section: Respiratorymentioning
confidence: 74%
See 4 more Smart Citations
“…The results of the study of Hastuti and Marnita, et al showed that the physiological development of infant breathing after treatment (post) in the intervention and control groups showed that there were significant differences in BBLR Infant Breathing after treatment (post) both in the intervention group and the control group. The results of this study showed that tactile-kinesthetic stimulation interventions affected infant breathing where the breathing of infants who were given tactile-kinesthetic stimulation was more stable than infants who were not stimulated, which was seen in the intervention group of average respiration before the intervention 11 .…”
Section: Respiratorymentioning
confidence: 74%
“…The condition of LBW causes the body's organs to not be able to function perfectly, so the adjustment of organ functions to the environment outside the womb is very difficult for babies 11 . With excessive changes in extrauterine conditions can cause stress in LBW.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations